2022
DOI: 10.3389/fmicb.2021.813993
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic Analysis Indicates That Oxidative Stress Is the Common Feature Triggering Antibiotic Production in Streptomyces coelicolor and in the pptA Mutant of Streptomyces lividans

Abstract: In most Streptomyces species, antibiotic production is triggered in phosphate limitation and repressed in phosphate proficiency. However, the model strain, Streptomyces coelicolor, escapes this general rule and produces actinorhoddin (ACT), a polyketide antibiotic, even more abundantly in phosphate proficiency than in phosphate limitation. ACT was shown to bear “anti-oxidant” properties suggesting that its biosynthesis is triggered by oxidative stress. Interestingly, Streptomyces lividans, a strain closely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(66 citation statements)
references
References 48 publications
1
52
0
Order By: Relevance
“…Since it was previously demonstrated that there is a negative correlation between total lipid content and antibiotic production in the ppk and pptA mutants of S. lividans [ 10 ], in S. coelicolor [ 5 ] as well as in other Streptomyces strains [ 11 ], we assessed the lipid content of the two strains grown on solid R2YE with no phosphate added for 72 h. The results shown in Figure 6 confirm that the total lipid content of the strain expressing the functional ATPase was significantly lower than that of the strain expressing the non-functional ATPase. These data confirmed, once again, the existence of a negative correlation between total lipid content and antibiotic production [ 5 , 6 , 11 ].…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…Since it was previously demonstrated that there is a negative correlation between total lipid content and antibiotic production in the ppk and pptA mutants of S. lividans [ 10 ], in S. coelicolor [ 5 ] as well as in other Streptomyces strains [ 11 ], we assessed the lipid content of the two strains grown on solid R2YE with no phosphate added for 72 h. The results shown in Figure 6 confirm that the total lipid content of the strain expressing the functional ATPase was significantly lower than that of the strain expressing the non-functional ATPase. These data confirmed, once again, the existence of a negative correlation between total lipid content and antibiotic production [ 5 , 6 , 11 ].…”
Section: Resultssupporting
confidence: 74%
“…These results confirmed the long known but mysterious link existing between phosphate limitation leading to a lowering of the ATP content and the triggering of antibiotic biosynthesis. The connections between the triggering of antibiotic production in the weak antibiotic producing strain, S. lividans , via the over-expression of an ATPase described in this study and the previously described specific metabolic features of S. coelicolor that are correlated with its strong ability to produce an antibiotic [ 5 , 6 , 7 , 8 ], led us to propose an entirely novel conception of the nature of the link between an ATP deficit, usually linked to a phosphate limitation, and the triggering of antibiotic biosynthesis in Streptomyces species.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Streptomyces coelicolor ( SC ) [ 6 ] and Streptomyces lividans ( SL ) [ 7 ] are the model strains extensively used to study the regulation of specialized metabolites biosynthesis since these closely related strains possess the same biosynthetic pathways directing the biosynthesis of three well-characterized bio-active specialized metabolites, calcium-dependent antibiotic (CDA), undecylprodigiosin (RED), and actinorhodin (ACT). However, these metabolites are mainly produced by SC [ 8 ] and, consistently, proteins encoded by genes of these pathways are far more abundant in SC than in SL [ 9 ]. In order to gain a better understanding of the different physiological and metabolic features underpinning the contrasted biosynthetic abilities of these two strains to produce antibiotics and of the impact of phosphate availability on the latter, an in-depth comparative analysis of the proteome of these two strains grown for 48 and 60 h on the solid modified R2YE medium either limited (1 mM) or proficient in Pi (5 mM), was carried out.…”
Section: Introductionmentioning
confidence: 99%